THE EFFECT OF USING GAMES IN IMPROVING SPEAKING SKILLS - Khaerunnisa, Khaerunnisa; Atmowardoyo, Haryanto; Sakkir, Geminastiti (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2022)
This iresearch ifocused ion ithe ieffect iof iusing igames iin iimproving ispeaking iskills iat iSMAN i6 iSidrap. iThe iresearcher iapplied ipre-experimental imethod iwith ione igroup ipretest-posttest idesign. iClass iXII iMIPA i2 ithat iconsists iof i29 istudents iwas ichosen ias ia isample iin ithis iresearch iusing icluster irandom isampling. iIn iorder ito icollect idata, ithe iresearcher iused iinterview ias ia ispeaking itest ito iknow ithe istudents’ ispeaking iability iin iterms iof iaccuracy, ifluency, iand icomprehensibility ibefore iand iafter iadministering ithe itreatment. iThe iresults iof ithis iresearch iindicated ithat ithe iuse iof igames iis ieffective iin iimproving istudents' ispeaking iskills.. iIt iwas iproved iby ithe iresult iof idata ianalysis iwhich ishowed ithat ithere iwas ia isignificant iimprovement ibetween ithe istudents’ iscore iin ipre-test iand ipost-test. iIn ithe ipost-test, ithe imean iscore iof ithe istudent iwas i56,55. iIt iwas ihigher ithan ithe imean iscore iin ithe ipre-test iwhich iwas i36.55. iTherefore, igames iare ieffective ito iimprove istudents' ispeaking iskills iin iterms iof iaccuracy, ifluency, iand icomprehension Keywords— Games, Speaking Skill.